Carbon dioxide tension as a reflection of different respiratory rates and chest x-ray features in children with community acquired pnemonia - Deddy Iskandar; Nastiti Noenoeng Rahajoe; Noenoeng Rahajoe; Imam Boediman (Indonesian Pediatric Society, 2010)
Background Diagnosis of community-acquired pneumonia (CAP) is often made based on clinical signs and symptoms as well as laboratory and radiographic tests. Several laboratory tests including blood gas analysis (BGA) can be helpful in establishing the diagnosis. The single most direct and useful BGA is the arterial carbon dioxide tension (PCO2). It directly reflects the adequacy of alveolar ventilation and indirectly could reflect the severity of illness.Objective To determine the differences of clinical signs and chest X-ray features in hospitalized CAP children with low PCO2 level and normal to high PCO2 level.Methods Patients with CAP in pediatric wards of Cipto Mangunkusumo Hospital who fulfilled the inclusion criteria were enrolled between July 2009 and November 2009. Patients were categorized as group with low PCO2 level (<35 mmHg) and group with normal to high PCO2 level (â‰¥ 35mmHg). All data, including clinical signs, laboratory results, and radiologic features on admissions were compared between groups.Results Thirty patients were enrolled; 20 patients belonged to low PCO2 level group and 10 patients belonged to normal-high PCO2 level group. Group with low PCO2 had significantly lower respiratory rate (P = 0.047), higher blood pH level (P = 0.044), and better chest X-ray features (P = 0.010) on admission compared to group with normal to high PCO2 level.Conclusion Low PCO2 level reflects better alveolar ventilation in children with CAP as described by lower respiratory rate and better chest X-ray features.